2014
DOI: 10.1007/s00381-014-2480-x
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical implications of Pott’s puffy tumor in children and adolescents

Abstract: All patients had epidural abscess, and one also presented subdural empyema. Five patients underwent drainage of all associated abscesses, bone resection, and sinusitis treatment. One was treated conservatively with broad-spectrum antibiotics, and no surgical intervention was required. All patients fully recovered their neurologic status, without further complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 42 publications
1
59
0
3
Order By: Relevance
“…These signs of osteomyelitis were absent in our patient’s case, and CT scan done 3 years prior to the presentation shows that frontal bone defect was present already at that time likely secondary to craniotomy and/or RTA 25 years ago (figures 7 and 8). Salomoa et al demonstrated their case series of six paediatric patients with PPT that frontal bone thickness erosions of variable size were identified in all CT head scans and intraoperatively in operated patients 5. No signs of osteomyelitis were identified intraoperatively in our patient’s case.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…These signs of osteomyelitis were absent in our patient’s case, and CT scan done 3 years prior to the presentation shows that frontal bone defect was present already at that time likely secondary to craniotomy and/or RTA 25 years ago (figures 7 and 8). Salomoa et al demonstrated their case series of six paediatric patients with PPT that frontal bone thickness erosions of variable size were identified in all CT head scans and intraoperatively in operated patients 5. No signs of osteomyelitis were identified intraoperatively in our patient’s case.…”
Section: Discussionsupporting
confidence: 49%
“…The infection spreads either directly through the sinus wall or by means of retrograde thrombophlebitis. The anterior wall and the floor of the frontal sinus are frequently the pathway of least resistance for the infection 5. In our patient, frontal sinus infection spread via patent roof of the frontal sinus to prefrontal soft tissue space following the pathway of least resistance and not spreading intracranially.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations